Synovial sarcoma cell lines showed reduced DNA repair activity and sensitivity to a PARP inhibitor. (28th June 2016) - Yamasaki, Hiroyuki; Miyamoto, Mamiko; Yamamoto, Yuki; Kondo, Tadashi; Watanabe, Toshiki; Ohta, Tsutomu
Abstract : Synovial sarcoma is a soft‐tissue sarcoma and a rare type of cancer. Unfortunately, effective chemotherapies for synovial sarcomas have not been established. In this report, we show that synovial sarcoma cell lines have reduced repair activity for DNA damage induced by ionizing radiation (IR) and a topoisomerase II inhibitor (etoposide). We also observed reduced recruitment of RAD51 homologue ( S. cerevisia e; RAD51) at sites of double‐strand breaks (DSBs) in synovial sarcoma cell lines that had been exposed to IR. These findings showed that synovial sarcoma cell lines are defective in homologous recombination (HR) repair. Furthermore, we found that a poly‐(ADP‐ribose) polymerase (PARP) inhibitor (AZD2281; olaparib) effectively reduced the growth of synovial sarcoma cell lines in the presence of an alkylating agent (temozolomide). Our findings offer evidence that treatment combining a PARP inhibitor and an alkylating agent could have therapeutic benefits in the treatment of synovial sarcoma. Abstract : We have demonstrated that two synovial sarcoma cell lines have reduced HR repair activity and that they are sensitive to a PARP inhibitor. Moreover, treating with both a PARP inhibitor and an alkylating agent directly enhanced the therapeutic benefit in the treatment of synovial sarcoma. We also found that the recruitment of RAD51 at DSB sites was deficient in synovial sarcoma cell lines.